Tailoring the grain boundary structure and chemistry of the dendrite-free garnet solid electrolyte Li6.1Ga0.3La3Zr2O12 - Rae-Hyun Lee; Chea-Yun Kang; Jong-Kyu Lee; Bong-Soo Jin; Kyong-Nam Kim; Hyun-Soo Kim; Jung-Rag Yoon; Seung-Hwan Lee (NPG Asia Materials)
Abstract Garnet-type Li6.1Ga0.3La3Zr2O12 (LGLZO) exhibits high ionic conductivity and extremely low electronic conductivity. The electrochemical properties strongly depend on the characteristics of the grain boundaries and pores in the oxide–ceramic electrolyte. Currently, the main issue of LGLZO is its large grain boundary resistance due to high-temperature sintering. Herein, we propose an effective method for reinforcing the chemical and structural characteristics of the grain boundaries using a Li2O-B2O3-Al2O3 (LBA) sintering aid. In this study, the LBA sintering aid is critical because it fills grain boundaries and void spaces. As a result, LGLZO solid-state electrolytes with sintering aids significantly enhance the ionic conductivity and reduce the activation energy, especially in the grain boundary region. Another crucial issue is the formation of Li dendrites in LGLZO. Since dendritic Li propagates along the grain boundaries, the optimized LGLZO solid-state electrolyte demonstrates excellent stability against Li metals. Overall, the LGLZO electrolyte with the LBA sintering aid exhibits stable long-term cycling performance due to the well-designed grain boundaries.